2016
DOI: 10.3906/biy-1501-30
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protein expression changes in the blood plasma of cows during the last month before parturition and 2 months after calving

Abstract: details of feeding shown in Table 1). Blood, the material for analysis, was drawn from the external jugular vein and collected using sterile needles and tubes with anticoagulant (EDTA K 3). Collection of samples was performed at the following points: 30, 14, and 7 days before parturition and 1, 7, 14, 30, and 60 days after calving. Blood was collected each time from the same animals, and groups were formed according to the sampling date; thus, each experimental group consisted of 10 animals. The total number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Glucose regulates the concentrations of other blood metabolites [6], and low blood glucose in the PPP causes repeat breeding and reduces the conception rate (CR) [7,8]. Many protein-related parameters are highly affected around parturition and may significantly impose to further reproductive performance [9]. Animals require minerals such as calcium (Ca), magnesium (Mg), and phosphorus (P) during late pregnancy and the postpartum period for growth, reproduction, and lactation, which often affect specific requirements and serve as catalytic components of enzymes or regulate several mechanism involved in pregnancy and lactation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose regulates the concentrations of other blood metabolites [6], and low blood glucose in the PPP causes repeat breeding and reduces the conception rate (CR) [7,8]. Many protein-related parameters are highly affected around parturition and may significantly impose to further reproductive performance [9]. Animals require minerals such as calcium (Ca), magnesium (Mg), and phosphorus (P) during late pregnancy and the postpartum period for growth, reproduction, and lactation, which often affect specific requirements and serve as catalytic components of enzymes or regulate several mechanism involved in pregnancy and lactation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Many protein-related parameters are highly affected around parturition and may significantly impose to further reproductive performance [Kurpińska et al 2015, Kurpińska et al 2016. Gonzales and Rocha [1998] reported that higher levels of urea and lower levels of protein are noted in cows with prolonged inter-pregnant period and Jorritsma et al [2003] underlined that urea may impact the oocyte development, fertilization and embryo development.…”
Section: Introductionmentioning
confidence: 99%
“…Kurpińska et al. () examined bovine plasma using 2DE and MS identification. Authors collected samples at similar time frames as in present study but identified different proteins—23 spots represented 13 identified proteins of 283 detected spots.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports about the analysis of periparturient plasma protein profile in cows but due to different sample protocols as well as different criteria for the selection of spots for identification, full profile was not established yet (Kurpińska, Jarosz, Ożgo, & Skrzypczak, ; Ma, Bu, Yang, Yan, & Wang, ; Yang et al., ).…”
Section: Introductionmentioning
confidence: 99%